Coprevalence of COVID-19 and Dengue fever in Pakistan: Co-revalence of COVID-19 and Dengue fever in Pakistan - Naeem, Usra; Mujtaba, Babar; Ikram, Atif; Naeem, Manzoor Ahmad; Badar, Syeda Asfara; Naeem, Aisha (Pakistan BioMedical Journal, 2022)
Pakistan is facing an epidemic of dengue fever amidst COVID-19 outbreak which is a serious public health concern. This article provides an overview of factors that could have led to an unexpectedly higher number of Dengue fever cases in Pakistan this year, such as, insufficient preventive measures to control Dengue at the national and domestic level, lack of surveillance system for the spread and control of the disease, and the lack of awareness among the general population regarding the possible outbreak of the disease. This situation has challenged the overburdened healthcare system of the developing country, which was still recovering from the immense pressure of COVID-19. This study also highlights the challenges faced by physicians regarding the diagnosis and treatment of patients who are coinfected with COVID-19 and Dengue fever. Early detection and accurate diagnosis are crucial for the management of patients with either of the disease. Authors have suggested a few measures that may help in improving the management and prognosis of patients coinfected with COVID-19 and Dengue fever. Additionally, we have also proposed a few strategies, that, if adapted at the national level may help in controlling the spread of Dengue fever in the future. For example, policies should be devised by the government for the implementation of preventive measures at the domestic level which was in practice before the outbreak of COVID-19.